Development of Explosion Box Learning Media in Islamic Religious Education Subject for Students of Junior High School - Fatmawati, Fatmawati; Muhaemin, Muhaemin; Hasriadi, Hasriadi (South Sulawesi Education Development (SSED), 2024)
Islamic Religious Education learning at S.M.P.N. 9 North Kolaka focuses on theory and textbooks without utilizing various learning media such as Explosion boxes. It causes a lack of student understanding. This study aims to 1) analyze the need for Explosion box media development, 2) design Explosion box media, 3) evaluate the validity of Explosion box media, and 4) measure the effectiveness of Explosion box media. The method used is R&D with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The study subjects were class VIII B SMPN 9 North Kolaka students, with data collection techniques through observation, interviews, questionnaires, and qualitative and quantitative data analysis. The study results showed that the Explosion box is valid and effective. Validation from media experts (91%), material experts (96%), and language experts (79%) showed that this media is feasible to use. Its effectiveness is also proven by an increase in student understanding by 89% based on tests. The development of this media has been proven to meet the validity criteria and effectively improve student learning outcomes.